Laboratory diagnostic value of neopterin measurements in patients with COVID-19 infection - Fuchs Dietmar (De Gruyter, 2021)
The new coronavirus SARS-CoV-2 was identified to be responsible for the COVID-19 pandemic. There are striking differences in the response to infection, some people develop no or mild symptoms, while other outcomes are severe of even fatal. For those COVID-19 patients who require hospitalization, prognostic markers could help clinicians to identify patients with a poor outcome early. The serum levels of the immune activation marker neopterin have already been shown to be of prognostic value in patients with SARS-CoV-1 and a similar pattern can be observed for SARS-CoV-2. This comment discusses the biochemical circuits that support the clinical value of neopterin measurements in COVID-19 patients.